Metformin modifies the exercise training effects on risk factors for cardiovascular disease in impaired glucose tolerant adults1. (16th March 2013) - Malin, Steven K.; Nightingale, Joy; Choi, Sung‐Eun; Chipkin, Stuart R.; Braun, Barry
Abstract Impaired glucose tolerant (IGT) adults are at elevated risk for cardiovascular disease (CVD). Exercise or metformin reduce CVD risk, but the efficacy of combining treatments is unclear. Objective: To determine the effects of exercise training plus metformin (EM), compared with each treatment alone, on CVD risk factors in IGT adults. Design and Methods: Subjects were assigned to placebo (P), metformin (M), exercise training plus placebo (EP), or EM (8/group). In a double‐blind design, P or 2, 000 mg/d of M were administered for 12 weeks and half performed aerobic and resistance training 3 days/week for ∼60 min/day at 70% pretraining heart rate peak. Outcomes included adiposity, blood pressure (BP), lipids, and high sensitivity C‐reactive protein (hs‐CRP). Z‐scores were calculated to determine metabolic syndrome severity. Results: M and EM, but not EP, decreased body weight compared with P (P < 0.05). M and EP lowered systolic blood pressure by 6% (P < 0.05), diastolic blood pressure by 6% (P < 0.05), and hs‐CRP by 20% (M: trend P = 0.06; EP: P < 0.05) compared with P. Treatments raised high‐density lipoprotein cholesterol (P < 0.05; EM: trend P = 0.06) compared with P and lowered triacyglycerol (P < 0.05) and metabolic syndrome Z‐score compared with baseline (EP; trend P = 0.07 and EM or M; P < 0.05). Conclusions: Although exercise and/or metformin improve some CVD risk factors, only training or metformin alone lowered hs‐CRP and BP. Thus, metformin may attenuate the effects of training on some CVD risk factors and metabolic syndrome severity in IGT adults.